2019
DOI: 10.1080/17453674.2019.1599777
|View full text |Cite
|
Sign up to set email alerts
|

Uncemented cups with and without screw holes in primary THA: a Swedish Hip Arthroplasty Register study with 22,725 hips

Abstract: Background and purpose — Uncemented cups in total hip arthroplasty (THA) are often augmented with additional screws to enhance their primary stability. We investigated whether there is a difference in the risk for revision between cups with screw holes and cups without screw holes. Patients and methods — We analyzed the risk for cup revision of uncemented cups registered in the Swedish Hip Arthroplasty Register (SHAR) between 2000 and 2017 with respe ct to the presence of screw holes. Only patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Acetabular cups without screw holes have a lower rate of revision compared to ones with screw holes, as shown by Otten et al in a study on 22,725 primary total hip replacements [12]. The authors showed that the rate of aseptic loosening was not statistically significant between the two, but a limitation of the study was a mean follow-up of only 3.4 years (0-18) [12].…”
Section: Designmentioning
confidence: 88%
“…Acetabular cups without screw holes have a lower rate of revision compared to ones with screw holes, as shown by Otten et al in a study on 22,725 primary total hip replacements [12]. The authors showed that the rate of aseptic loosening was not statistically significant between the two, but a limitation of the study was a mean follow-up of only 3.4 years (0-18) [12].…”
Section: Designmentioning
confidence: 88%
“…An earlier study has reported uctuations in the inclination and shape of the acetabular cup following screw insertion [24]. Notably, the risk of acetabular cup revision using screw holes is higher in patients with primary osteoarthritis [24][25]. The inclination and angle of patients are different, and balance must be achieved between restoring the original anatomical structure of patients and establishing stable joints [26].…”
Section: Discussionmentioning
confidence: 99%